Dust Activities Induced by Nocturnal Low‐Level Jet Over the Taklimakan Desert From WRF‐Chem Simulation. Issue 12 (20th June 2022) - Han, Zihang; Ge, Jinming; Chen, Xingyu; Hu, Xiaoyu; Yang, Xuan; Du, Jiajing
Abstract: The formation and pronounced diurnal variation of the nocturnal low‐level jet (NLLJ), and the dust activities associated with the NLLJ over the Taklimakan Desert (TD) are revealed by the simulations from a coupled meteorology‐chemistry model WRF‐Chem. Based on the model diagnostic analysis, it is found that the NLLJ is mainly induced by the oscillation of the Coriolis force and the turbulent mixing largely accounts for the diurnal change of NLLJ over the TD. Moreover, the Hovmöller diagram indicates that a maximum dust emission exists in the early morning and dust western propagation mode frequently occurs at night. To further analyze the causal relationship between the morning dust emission and transport with NLLJ, the scale height of momentum ( H ) is conducted to describe the momentum vertical distribution and the surface friction velocity is used to reflect the intensity of dust flux. It is found that the downward momentum of NLLJ is transferred from the atmosphere to the ground and induces dust emissions after sunrise. Combined with potential temperature and turbulent kinetic energy (TKE) analysis, turbulent mixing dominated by solar surface heating contributes to this process. Given these findings, dust emission caused by NLLJs appears to be an essential driving factor for reviving dust activities and the NLLJs can facilitate the long‐range transmission of dust particles due to the topography throughout summer. Key Points: Nocturnal low‐level jet (NLLJ) formation and variation over the Taklimakan Desert (TD) are captured by a high‐resolution WRF‐Chem model Downward mixing of NLLJ momentum in the midmorning significantly affects dust emission over the TD Dust transport by the NLLJ can be carried out for a long distance and a wide region under the surrounding high plateau topography effect